A Phenomenological Study: Speaking Anxiety Overwhelms English Learners - Hutabarat, Asna; Simanjuntak, Debora Chaterin (LPPM Universitas Advent Indonesia, 2019)
This study aims to determine the sources that cause speaking anxiety overwhelms English learners. It is qualitative in nature and focuses on learners’ speaking anxiety. The samples of the research are composed of senior high school students who deal with speaking anxiety. The primary data-gathering method is interview through semi-structured questions. The data were collected by in-depth face-to-face interview with 10 participants; the data were analyzed by determining the themes and description. The gathered data were analyzed using coding and verbatim quotes from research respondents. The results show 3 themes regarding sources that cause Speaking anxiety: Limitations of English Exposure, Fear of Negative Evaluation, and Learning Condition. It is undeniable that attitude holds an imperative role in learning to speak English. The results show two themes regarding learners’ attitude in causing them to become anxious whenever they speak English; the themes are self-inferiority and fear of making mistakes. Despite sources that cause learners to be anxious in speaking English, they find ways to reduce their anxiety in speaking English and from this study, there are two themes found regarding ways to reduce anxiety; they are: Media intervention and Establish learning support. Â Keywords: Speaking Anxiety, Negative Evaluation, speaking skills Â